Magnetotail response during a strong substorm as observed by GEOTAIL in the distant tail - Belehaki, A.; Mcentire, R. W.; Kokubun, S.; Yamamoto, T. (CCSD, 1998)
International audience Simultaneous energetic particle and magnetic field observations from the GEOTAIL spacecraft in the distant tail (X GSM ? ?150 Re) have been analysed to study the response of the Earth's magnetotail during a strong substorm (AE ? 680 nT). At geosynchronous altitude, LANL spacecraft recorded three electron injections between 0030 UT and 0130 UT, which correspond to onsets observed on the ground at Kiruna Ground Observatory. The Earth's magnetotail responded to this substorm with the ejection of five plasmoids, whose size decreases from one plasmoid to the next. Since the type of magnetic structure detected by a spacecraft residing the lobes, depends on the Z extent of the structure passing underneath the spacecraft, GEOTAIL is first engulfed by a plasmoid structure; six minutes later it detects a boundary layer plasmoid (BLP) and finally at the recovery phase of the substorm GEOTAIL observes three travelling compression regions (TCRs). The time-of-flight (TOF) speed of these magnetic structures was estimated to range between 510 km/s and 620 km/s. The length of these individual plasmoids was calculated to be between 28 Re and 56 Re. The principal axis analysis performed on the magnetic field during the TCR encountered, has confirmed that GEOTAIL observed a 2-D perturbation in the X-Z plane due to the passage of a plasmoid underneath. The first large plasmoid that engulfed GEOTAIL was much more complicated in nature probably due to the external, variable draped field lines associated with high beta plasma sheet and the PSBL flux tubes surrounding the plasmoid. From the analysis of the energetic particle angular distribution, evidence was found that ions were accelerated from the distant X -line at the onset of the burst associated with the first magnetic structure.